PENERAPAN ALGORITMA GENETIKA DALAM MENENTUKAN JALUR TERDEKAT PENDISTRIBUSIAN PRODUK GRANIT/KERAMIK PADA PT. CHANG JUI FANG - NASUTION, ADNAN BUYUNG (STMIK KAPUTAMA, 2019)
PT.Chang Jui Fang as the only ceramics industry producer in North Sumatra has many distributor locations, the problem so far is the difficulty in choosing the location of the distributor city to be targeted to optimize or determine the shortest path in the distribution journey based on distributor needs, the application of genetic algorithms with the system builds a new population of the second parent crossing that produces a new chromosome as the shortest path optimization as a solution to the problem.